2013
DOI: 10.11118/actaun201260060293
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of different garlic varieties by dry bulb mite Aceria tulipae (Keifer) (Acari: Eriophyidae)

Abstract: The intensity of garlic infestation by dry bulb mite Aceria tulipae (Keifer, 1938) was observed on different garlic varieties in central Moravia. The aim of this study was to determine infestation of different garlic varieties during storage in the winter period 2011–2012. Current studies on 11 garlic varieties from the Centre of the Region Haná at an altitude of 210 m showed high abundance of Aceria tulipae on 10 varieties. Bolting garlic varieties (Bzenecky Mutant VF, Sochi 25, Tiraspol, Zailijskij) were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, a Polish DBM population colonized a different onion variety (including white) with great success (Skoracka et al 2014 ). This may suggest the existence of genetic diversity within A. cepa for susceptibility to DBM, as was shown for various garlic varieties in Czechia (Sapáková et al 2012 ); this possibility merits further investigation. Moreover, the population growth rate on red onion was lower in our studies when compared to results reported by Skoracka et al ( 2014 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, a Polish DBM population colonized a different onion variety (including white) with great success (Skoracka et al 2014 ). This may suggest the existence of genetic diversity within A. cepa for susceptibility to DBM, as was shown for various garlic varieties in Czechia (Sapáková et al 2012 ); this possibility merits further investigation. Moreover, the population growth rate on red onion was lower in our studies when compared to results reported by Skoracka et al ( 2014 ).…”
Section: Discussionmentioning
confidence: 62%
“…In addition to its great economic importance, there is increasing interest in A. tulipae as a study subject for basic and applied research. Experimental studies have focused on developmental time of DBM on garlic (Courtin et al 2000 ), DBM infestation ability of various garlic varieties (Sapáková et al 2012 ), methods of genetic identification of mites (Hein et al 2012 ), impact of DBM on garlic production (Debnath and Karmakar 2013 ) and methods of biological control of DBM (Leśna et al 2014 ). However, current knowledge of DBM host range is largely anecdotal.…”
Section: Introductionmentioning
confidence: 99%
“…The observed phenotypes of leaf deformations are assumed to protect the free roaming and no gall forming mites from dehydration. Under suitable environmental conditions, mites can proliferate to high numbers (Sapáková et al 2012). In addition, no leek plants developed mosaic symptoms and they tested negative for allexiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that high infestations of garlic cloves can result in a 32% loss in bulb crops (Budai et al 1997;Debnath and Karmakar 2013). High population densities of DBM have been reported on the bulb segment and middle sections of leaves (Sapáková et al 2012;Beltran 2020). Once established on bulbs or leaves, mites can develop high population density.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mites transmit different viruses of genus Allexivirus [ 128 , 129 , 130 ]. Bolting varieties of garlic have been reported to be more susceptible to mite attack than non-bolting ones [ 131 ]. Insects from several orders, such as Ephestia cautella (Lepidoptera), Delia antiqua (Diptera) or Thrips tabaci (Thysanoptera), feed on the plants or stored bulbs and cause important yield losses [ 132 , 133 ].…”
Section: Pathogens Of Garlic: Threats Treatments and Perspectivesmentioning
confidence: 99%